(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Talent acquisition and recruitment play a critical role in the success of organizations. In this paper, we review the current developments, challenges, and best practices in skills acquisition and recruitment. The examine is primarily based on a overview of the literature and analysis of data collected from various assets, which includes surveys, interviews, and case research. Our findings show that the major trends in talent acquisition and recruitment include the increasing use of technology, the emphasis on diversity and inclusion, and the growing importance of employer branding. The important challenges include the dearth of professional skills, the changing nature of labor, and the increasing competition for expertise. To address these challenges, organizations need to adopt best practices such as developing a comprehensive talent strategy, leveraging technology for recruitment and talent management, and focusing on employer branding and employee experience. Our study provides insights and recommendations for HR practitioners and managers involved in talent acquisition and recruitment.